Reliability of a two‐dimensional demand‐based networked system with multistate components. (18th June 2020) - Xiao, Hui; Yi, Kunxiang; Kou, Gang; Xing, Liudong
Abstract: Existing research on multistate system reliability has mainly focused on one‐dimensional systems such as parallel systems, linear sliding window systems, and linearly consecutively connected systems. However, two‐dimensional networked systems widely exist in real‐world applications such as lighting systems, monitoring systems, and computer network systems. This research considers a two‐dimensional networked system consisting of multistate components. The system fails if the cumulative performance of any row or any column cannot meet a predetermined demand. A novel reliability evaluation algorithm is proposed for the considered two‐dimensional networked system by extending the universal generating function technique. Furthermore, the proposed model and reliability evaluation algorithm are extended to a two‐dimensional networked system with phased missions. The proposed models and algorithms are illustrated by a matrix heating system in a thermoforming machine.